2018 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2018
DOI: 10.23919/date.2018.8342278
|View full text |Cite
|
Sign up to set email alerts
|

Memristive devices for computation-in-memory

Abstract: CMOS technology and its continuous scaling have made electronics and computers accessible and affordable for almost everyone on the globe; in addition, they have enabled the solutions of a wide range of societal problems and applications. Today, however, both the technology and the computer architectures are facing severe challenges/walls making them incapable of providing the demanded computing power with tight constraints. This motivates the need for the exploration of novel architectures based on new device… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
(41 reference statements)
0
41
0
Order By: Relevance
“…MAP is one of the most successful hardware implementations of Non-deterministic Finite Automata (NFA), whose high efficiency has been proved by many researches [2][3][4][5][6][7]12]. Recent works such as Cache Automaton [16] and RRAM-AP [17] intend to improve MAP by using different memory technologies while maintaining its basic structure. These designs have the following features in common:…”
Section: Automata Processorsmentioning
confidence: 99%
See 2 more Smart Citations
“…MAP is one of the most successful hardware implementations of Non-deterministic Finite Automata (NFA), whose high efficiency has been proved by many researches [2][3][4][5][6][7]12]. Recent works such as Cache Automaton [16] and RRAM-AP [17] intend to improve MAP by using different memory technologies while maintaining its basic structure. These designs have the following features in common:…”
Section: Automata Processorsmentioning
confidence: 99%
“…Therefore, this pipeline stage is the bottleneck that limits Cache Automaton's speed and throughput. RRAM-AP concept [17] shows the potential of building an automata accelerator using Resistive Random Access Memory (RRAM) arrays, which are even faster than SRAM arrays. However, a complete design was not given.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, efficient neuromorphic circuits have been designed using ReRAM devices [69][70][71][72], that use analog operations on crossbar arrays. Analog matrix operations have also been realized using ReRAM crossbar arrays [73,74]. Furthermore, it has been demonstrated that traditional applications such as image processing can also benefit from logic-inmemory computations using ReRAM [75].…”
Section: Figure 28mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that traditional applications such as image processing can also benefit from logic-inmemory computations using ReRAM [75]. Novel application specific processor for automata processing have also been realized using crossbar arrays [74]. realize material implication and suggested their use for logic-in-memory operations, but no architecture was proposed [79].…”
Section: Figure 28mentioning
confidence: 99%